Insights from the past: Invasion trajectory and niche trends of a global freshwater invader - Guareschi, S; Cancellario, T; Oficialdegui, F J; Clavero, M (Global change biology, 2024)
Freshwater ecosystems are invaded by a non-random selection of taxa, among which crayfish stand out with successful examples worldwide. Species distribution models (SDMs) have been used to detect suitable areas for invasive species and predict their potential distributions. However, these prediction exercises assume the stability of realized environmental niches, which is uncertain during invasion. Worldwide evaluations involving cosmopolitan invaders may be particularly useful but have seldom been considered. Focusing on the successful invasion history of the red swamp crayfish, Procambarus clarkii, we assessed its geographic expansion and niche trends over time. Based on global occurrences from 1854 to 2022, multiple sequential SDMs have been implemented based on a set of bioclimatic variables. The environmental suitability for each period was projected through to the next period(s) using an ensemble procedure of commonly used SDM algorithms. As the records of the species are known, it was possible to check whether the modelling projections were concordant with the observed expansion of red swamp crayfish at a global scale. This also permitted analysis of its realized niche, and its dynamics, during different expansion phases. SDM maps based on past species records showed concordance with the known crayfish distributions and yielded similar spatial patterns with outputs overperforming random combinations of cells in term of suitability. The results also reflect the stability of the species niche, which despite some expansions during the invasion process, changed little in terms of main position in functional space over time. SDMs developed in the early stages of invasion provide useful insights but also tend to underpredict the potential range compared to models that were built for later stages. Our approach can be easily transferable to other well-documented taxa and represents valuable evidence for validating the use of SDMs, considering a highly dynamic world where biogeographical barriers are often bypassed.
Keywords: zavlečené druhy; invasive crayfish; sladká voda; global distribution; severní raci; Animals; niche conservatism; Astacoidea; Introduced Species; Fresh Water; Procambarus clarkii; biological invasions; zvířata; invasion history; ekosystém; Ecosystem